Main Development Directions of Agricultural Areas in the Eastern Zangezur Region - Mammadova Sheker; Abdurahmanov Faig; Humbatov Mahmud (BIO Web of Conferences)
The territories of the East Zangezur region, including the Kalbajar, Lachin, Gubadli, Zangilan and Jebrail districts, with their rich natural resources, biodiversity, breathtaking nature, favorable climate and agro-climatic conditions, complex geological structure and diverse landforms have attracted the attention of travelers and researchers since ancient times, which led to the study of this area. The region, predominantly mountainous, is of great importance for the development of agricultural industries and achieving high productivity. Favorable climatic and relief conditions, along with fertile soils, play an invaluable role in the development of both crop production and livestock farming. Since Soviet times, the territory has been used for agricultural purposes, fully meeting the country's needs for milk, meat and grain products. This article highlights the main factors in the development of agricultural industries within the region and examines their spatial distribution, zoning and a map-scheme.